Plastic and heritable variation in shell thickness of the intertidal gastropod Nucella lapillus associated with risks of crab predation and wave action, and sexual maturation - Pascoal, Sonia (2019)
The intertidal snail Nucella lapillus generally has thicker shells at sites sheltered from wave action, where crabs are abundant and pose a high risk of predation, than at exposed sites where crabs are rare. We studied two populations showing the opposite trend. We reciprocally transplanted snails between field sites and measured shell length, width and lip thickness of those recaptured 12 months later. Snails transplanted to the sheltered site grew larger than sheltered-site residents, which in turn grew larger than transplants to the exposed site. Relative shell-lip thickness was greater in residents at the exposed site than at the sheltered site. Transplants from shelter to exposure developed relatively thicker shells than their controls and relatively thinner shells from exposure to shelter. Progeny of the two populations were reared for 12 months in a common garden experiment presenting effluent from crabs feeding on broken conspecifics as the treatment and fresh sea-water as the control. The crab-effluent treatment decreased foraging activity, concomitantly reducing cumulative somatic growth and reproductive output. Juveniles receiving crab-effluent grew slower in shell length while developing relatively thicker shell lips than controls, the level of response being similar between lineages. F(2) progeny of the exposed-site lineage showed similar trends to the F(1)s; sheltered-site F(2)s were too few for statistical analysis. At sexual maturity, shell-lip thickness was greater in snails receiving crab-effluent than in controls, indicating plasticity, but was also greater in the exposed-site than in the sheltered-site lineage, indicating heritable variation, probably in degree of sexual thickening of the shell lip. Results corroborate hypotheses that 'defensive' shell thickening is a passive consequence of starvation and that heritable and plastic control of defensive shell morphology act synergistically. Shell thickening of juveniles was similar between lineages, contrary to hypotheses predicting differential strengths of plasticity in populations from low- or high-risk habitats.